2015
DOI: 10.1152/jn.00682.2014
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable influences of primary auditory cortex and the posterior auditory field on neuronal responses in the dorsal zone of auditory cortex

Abstract: Kok MA, Stolzberg D, Brown TA, Lomber SG. Dissociable influences of primary auditory cortex and the posterior auditory field on neuronal responses in the dorsal zone of auditory cortex. J Neurophysiol 113: 475-486, 2015. First published October 22, 2014 doi:10.1152/jn.00682.2014.-Current models of hierarchical processing in auditory cortex have been based principally on anatomical connectivity while functional interactions between individual regions have remained largely unexplored. Previous cortical deactiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
(104 reference statements)
0
5
0
Order By: Relevance
“…Activity of DZ neurons is based on the interplay of intrinsic neuronal properties, local circuit processing and input signals. As expected from the dominant presence of auditory responsivity, inputs to DZ largely arise from auditory cortical and thalamic regions (Kok et al, 2015; Winer et al, 2001). However, a report by Kok et al (2013) identified projections from 18 visual cortical areas whose inputs represented >38% of the total cortical inputs to DZ.…”
Section: Discussionmentioning
confidence: 92%
“…Activity of DZ neurons is based on the interplay of intrinsic neuronal properties, local circuit processing and input signals. As expected from the dominant presence of auditory responsivity, inputs to DZ largely arise from auditory cortical and thalamic regions (Kok et al, 2015; Winer et al, 2001). However, a report by Kok et al (2013) identified projections from 18 visual cortical areas whose inputs represented >38% of the total cortical inputs to DZ.…”
Section: Discussionmentioning
confidence: 92%
“…Most studies to date aimed to inactivate primary AC (A1) as it is most clearly stereotaxically- and cytoarchitectonically-defined and is the region with most well-defined homologues in other species [ 32 ]. The hierarchical organisation of auditory cortex means that disrupting primary cortex will additionally perturb processing in non‐primary areas [ 33 , 34 ]. Despite A1 being the most frequently targeted inactivation site, the trade-off between incomplete inactivation within an area and nonspecific effects beyond a target area make it likely that non‐primary auditory fields ( Figure 1 A) are usually at least partially affected as well, thus obfuscating the exact role of A1.…”
Section: Challenges In Defining Auditory Cortex Functionmentioning
confidence: 99%
“…With proper use and care, implanted cryoloops can be cooled routinely for many years. These cortical cooling procedures can be adapted to other behavioral paradigms 10,11,12 or electrophysiological recording preparations 13,14 in alternative animal models 15,17,18,22 .…”
Section: Discussionmentioning
confidence: 99%
“…. NOTE: This can be verified with thermocline mapping 12 or with a thermal imaging camera 13,14,19 .…”
Section: Verifying the Extent Of Coolingmentioning
confidence: 99%
See 1 more Smart Citation